Circadian change in bronchial responsiveness and airflow obstruction in asthmatic children. Issue 10 (October 1989) - van Aalderen, W M; Postma, D S; Koëter, G H; Knol, K
Abstract : To throw light on the question of whether the increase in bronchial responsiveness seen during the night is due to increased airflow obstruction, nine asthmatic children with increased airflow obstruction at night (group 1) were compared with nine without (group 2). The mean fall in forced expiratory volume in one second (FEV1) between 16.00 and 04.00 hours was 21.9% in group 1 and 2.3% in group 2. Selection of patients was based on the amplitude of change in peak expiratory flow (PEF) measured every four hours for three consecutive days at home. The study was performed in hospital on four consecutive days. Medication was withheld for three days before and during the measurements at home and in hospital. On the first day in hospital (day 4) FEV1 was measured every four hours for 24 hours. On day 6 inhaled histamine provocation tests were performed at the same times as the FEV1 measurements on day 4. Both groups showed a nocturnal fall in the provocative dose of histamine causing a 20% fall in FEV1 (PC20). The mean change in histamine PC20 from 16.00 to 04.00 hours was 1.1 doubling doses of histamine in group 1 and 1.5 doubling doses in group 2. The results indicate that the increase in nocturnal bronchial responsiveness that occurs at night is not due to an increase in airflow obstruction.